Laser diodes in holographic optical tweezers - Drobczyński, Sławomir; Masajada, Jan; Woźniak, Marta; Ziółkowski, Piotr (Photonics Letters of Poland, 2014)
Laser diodes are attractive sources of laser radiation in terms of price, size, controllability and availability of a wide spectrum of light emitted wavelengths. In this paper we present the use of three types of laser diodes in the holographic optical tweezers. We showed that they can be applied for effective trapping and live cells manipulation, despite their relatively small power. Full Text: PDF References D. Stevenson, F. Gunn-Moore, K. Dholakia, "Light forces the pace: optical manipulation for biophotonics", J. Biomedical Optics 15(4), 041503-1-041503-21 (2010). CrossRef K. Neuman, S. Blocka, "Optical trapping", Rev. Sci. Instrum. 75 (9), 2787 (2004). CrossRef R. Afzal, E. B. Treacy, "Optical tweezers using a diode laser", Rev. Sci. Instrum. 63 (4), 2157 (1992). CrossRef Z. Ulanowski, I. Ludlow, "Compact optical trapping microscope using a diode laser", Meas. Sci. Technol. 11, 1778 (2000). CrossRef M. Sery, Z. Lostak, M. Kalman, P. Jakl, P. Zemanek, "Compact laser tweezers", Proc. SPIE 6609, 66090N-1 (2007). CrossRef R.L. Eriksen, V. Ricardo, J. Glückstad, "Fully dynamic multiple-beam optical tweezers", Opt. Expr. 10 (14), 597 (2002). CrossRef D. Cojoc, V. Garbin, E. Ferrari, L. Businaro, F. Romanato, E. Di Fabrizio, "Laser trapping and micro-manipulation using optical vortices", Microelectr. Eng. 78?79, 125 (2005). CrossRef D. McGloin, K. Dholakia, "Bessel beams: Diffraction in a new light", Cont. Phys. 46(1), 15 (2005). CrossRef K. Berg?S?rensen, H. Flyvbjerg, "Power spectrum analysis for optical tweezers", Rev. Sci. Instrum. 75(3), 594 (2004). CrossRef W. Singer, S. Bernet, N. Hecker, M. Ritsch-Marte, "Three-dimensional force calibration of optical tweezers", J. Modern Optics 47 (14/15), 2921 (2000). CrossRef Ch.H.J. Schmitz, J.P. Spatz, J.E. Curtis, "High-precision steering of multiple holographic optical traps", Opt. Expr. 13 (21), 8678 (2005). CrossRef R.W. Bowman, G. Gibson, D Carberry, L. Picco, M. Miles, M.J. Padgett, "iTweezers: optical micromanipulation controlled by an Apple iPad", J. Opt. 13, 044002 (2011). CrossRef J. Liesener, M. Reicherter, T. Haist, H.J. Tiziani, "Multi-functional optical tweezers using computer-generated holograms", Opt. Comm. 185 (1-3), 77 (2000). CrossRef D.G. Grier et al., "Computer-generated holographic optical tweezer arrays", Rev. Sci. Instrum. 72 (3), 1810 (2001). CrossRef J.E. Curtis, Ch.H.J. Schmitz, J.P. Spatz, "Symmetry dependence of holograms for optical trapping", Opt. Lett. 30(16), 2086 (2005). CrossRef T. Cizmar, M. Mazilu, K. Dholakia, "In situ wavefront correction and its application to micromanipulation", Nature Phot. 4, 388 (2010). CrossRef